Hiccups in neurocritical care - Rajagopalan, Vanitha; Sengupta, Deep; Goyal, Keshav; Dube, Surya Kumar; Bindra, Ashish; Kedia, Shweta (Journal of neurocritical care, 2021)
Hiccups are usually self-limiting and benign but can be distressing when they become persistent or intractable and produce significant morbidity. In the intubated patients in neurocritical care, persistent hiccups may cause respiratory alkalosis and are also associated with an increased incidence of ventilator-associated pneumonia. Several pharmacological and nonpharmacological strategies have been devised for the treatment of persistent and intractable hiccups. The evidence to support or declare any intervention as harmful is scarce. In this review, we have presented the pathophysiology and workup, and a stepwise management protocol for intractable hiccups.